Pembuatan POC Pada Bank Sampah Pematang Pudu Bersih Kecamatan Mandau Kabupaten Bengkalis - Prama Widayat; Ryan Pahlawan; Safrul Rajab (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
Mandau District is one of the most densely populated districts in Bengkalis Regency, here there is a Pematang Pudu Clean Waste Bank located in Pematang Pudu village with a population of 29,986 people consisting of 17 RW and 95 RT with an area of 25 KM2. This waste bank was established in 2015 and accommodates non-organic waste such as bottles, plastic, paper, and cardboard of various types. However, organic waste that has not been maximized for processing is therefore given training on the manufacture of POC or Liquid Organic Fertilizer by involving the Adiwiyata school in Mandau District so that the benefits are felt to be wider and can be practiced at home to process organic waste.